Extraction Optimization of Crocin from Gardenia (Gardenia jasminoides Ellis)Fruits Using Response Surface Methodology and Quality Evaluation of Foam-Mat Dried Powder - Nguyen Minh Thuy; Pham Huynh Nhu; Ngo Van Tai; Vo Quang Minh (My University, 2022)
The crocin in gardenia, as a medical plant, has drawnthe attention of researchers and scientists due to its color and high antioxidant activity. To optimize the extraction parameters of crocin from gardenia fruits, response surface methodology (RSM) was employed.The effects of four independent variables, namely extraction temperature (45–55 °C), time (40–60 min), percentage of gardenia fruits(15–25%), and ethanol concentration (50–60%),on a crocin compound were investigated. The extract from the gardenia fruit was dried at different temperatures (55–70 °C) by the foam-mat drying method. The optimal extraction parameters were an extraction temperature of 55 °C, time of 57 min, percent of fruits in solvent at 24%, and an ethanol concentration of 56%. The results showed that the dried gardenia powder had maintained the crocin content well(6.64 mg/g), and the product with low water activity and moisture content of 0.33 and 5.72%, respectively, is suitable for storage. The foam-mat dried product also maintains the natural color and characteristics inherent in the raw materials, which could also be used as supplemental ingredients for other food industries.
Keywords: Gardenia jasminoides; Gardenia; Crocetin; Saffron Plant Research Studies